Revisiting thyroid hormones in schizophrenia - Santos, Nadine Correia (2012)
Thyroid hormones are crucial during development and in the adult brain. Of interest, fluctuations in the levels of thyroid hormones at various times during development and throughout life can impact on psychiatric disease manifestation and response to treatment. Here we review research on thyroid function assessment in schizophrenia, relating interrelations between the pituitary-thyroid axis and major neurosignaling systems involved in schizophrenia’s pathophysiology. These include the serotonergic, dopaminergic, glutamatergic, and GABAergic networks, as well as myelination and inflammatory processes. The available evidence supports that thyroid hormones deregulation is a common feature in schizophrenia and that the implications of thyroid hormones homeostasis in the fine-tuning of crucial brain networks warrants further research.